Self-rated physical fitness predicts cardiovascular and all-cause mortality: implications for clinical decision-making : sports cardiology - Moissl-Blanke, Angela P.; Delgado Gonzales de Kleber, Graciela; Kleber, Marcus E.; Mooren, Frank C.; Schäfer, Hendrik; Krämer, Bernhard; März, Winfried; Schmitz, Boris (European journal of preventive cardiology, 2025)
The study investigated the association between self-reported physical fitness (SRPF) and mortality in 3248 participants of the Ludwigshafen Risk and Cardiovascular Health (LURIC) study with a mean follow-up of 9.9 years.Self-reported physical fitness was inquired using an 11-point Likert scale on a paper-pencil questionnaire at enrolment, and we defined five distinct classes. Kaplan-Meier survival analysis and Cox regression models were used to investigate the association with mortality. Participants with higher baseline SRPF had a significantly lower risk of all-cause and cardiovascular mortality. Regarding cardiovascular mortality, participants in the highest SRPF class had the lowest risk with a hazard ratio of 0.14 (95% CI 0.08-0.24) compared with the lowest SRPF class. These associations remained statistically significant after adjustment for age, sex, hypertension, diabetes mellitus, low-density lipoprotein cholesterol, glycated haemoglobin A1c (HbA1c), smoking, and other confounders, including comorbidities. Similar results were seen in both participants with angiographically documented coronary artery disease (CAD, n = 2583, 78%) and those without CAD (n = 733; 22%). Higher SRPF was associated with significantly lower systolic blood pressure and resting heart rate as well as lower HbA1c, fasting glucose, serum uric acid, and lower inflammatory markers such as high-sensitive-C-reactive protein, interleukin-6, and serum amyloid A. Conversely, a higher SRPF was associated with higher apolipoprotein A-2 and high-density lipoprotein cholesterol concentrations (P < 0.001).Our research shows that SRPF is a strong predictor of overall and cardiovascular mortality for individuals with and without CAD. This suggests that SRPF should be part of routine medical check-ups, highlighting the importance of promoting physical activity for cardiovascular health.This study shows that self-reported physical fitness (SRPF) is a strong predictor of mortality, with higher self-rated fitness linked to lower risks of both all-cause and cardiovascular mortality, independent of other risk factors.Low SRPF is significantly associated with increased risk of all-cause and cardiovascular mortality, suggesting it may be an important indicator for health outcomes.High SRPF shows a protective association, highlighting its potential as an accessible, low-cost tool for promoting cardiovascular health in routine medical assessments.